1982
DOI: 10.1104/pp.69.2.411
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Polyamine Biosynthesis to the Initiation of Sprouting in Potato Tubers

Abstract: The polyamines putrescine, spermidine, and spermine and their biosynthetic enzymes arginine decarboxylase, ornithine decarboxylase and Sadenosyl-L-methionine decarboxylase are present in all parts of dormant potato (Solamm tuberosum L.) tubers. They are equally distributed among the buds of apical and lateral regions and in nonbud tissues. However, the breaking of dormancy and initiation of sprouting in the apical bud region are accompanied by a rapid increase in ornithine decarboxylase and Sadenosyl-L-methion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0
2

Year Published

1984
1984
1995
1995

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 22 publications
4
48
0
2
Order By: Relevance
“…Misidentification of the Agm peak in the original report (3) may require reevaluation of some data presented in later studies employing this HPLC method (4,8). For example, Kaur-Sawhney et al (8) reported a nearly fivefold increase in Agm titers of apical bud tissues of potato tubers during sprouting, although ADC activity in these tissues did not increase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Misidentification of the Agm peak in the original report (3) may require reevaluation of some data presented in later studies employing this HPLC method (4,8). For example, Kaur-Sawhney et al (8) reported a nearly fivefold increase in Agm titers of apical bud tissues of potato tubers during sprouting, although ADC activity in these tissues did not increase.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Kaur-Sawhney et al (8) reported a nearly fivefold increase in Agm titers of apical bud tissues of potato tubers during sprouting, although ADC activity in these tissues did not increase. However, a fivefold increase in ODC activity was observed to accompany markedly elevated PA levels in these tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Arginine is converted by ADC2 to agmatine which is then converted to putrescine (1,11,12). In recent studies by Heimer et al (10) and Cohen et al (6) on tomato ovaries and fruits, it was observed that the activity of ODC changed during fruit development, whereas the relatively low '…”
Section: Abstracrmentioning
confidence: 99%
“…Assim sendo, elevados níveis de poliaminas são necessários durante a embriogênese de cenoura em cultura de tecidos (FEIRER, et al, 1984). Os níveis de poliaminas livres e conjugadas aumentaram drasticamente durante a diferenciação e regeneração de plantas derivadas do mesofilo de Vigna em cultura deprotoplastos (KAUR-SAWHNEY et al, 1982). A formação de novas células está correlacionada com o aumento na síntese de DNA, RNA, proteínas e com a formação de poliaminas (COHEN et al, 1982).…”
Section: Introductionunclassified